Silk : processing, properties and applications - Murugesh Babu, K. (Woodhead publishing in textiles, 2013)
Silk is a natural, environmentally-friendly fibre with a remarkable range of properties, making it ideal for use in apparel and many other applications. Silk: Processing, properties and applications provides an authoritative reference on sericulture, silk fabric processing, silk properties and its applications. The book begins by looking at key aspects of sericulture, including the range of mulberry and non-mulberry species of silk worm, early and late stage rearing and harvesting of cocoons. Further chapters discuss reeling, weaving and spinning techniques as well as dyeing. The book also discusses the physical and chemical structure of silk as well as its mechanical and thermal properties. Concluding chapters discuss developments in applications and the properties of spider silk. Silk: Processing, properties and applications is useful for textile technologists, fibre scientists and all those with an interest in the characteristics of silk, its production and the varied uses of this important fibre. Provides an in-depth summary of silk production, properties and structure-property relationshipsExamines the future of silk, including its application in the textile, biomedical, pharmaceutical and cosmetic industriesProvides an authoritative reference on sericulture, silk fabric processing, silk properties and its applications.